Analisis Validasi Keterampilan Komunikasi Dan Argumentasi Siswa Biologi SMA Kelas XI MIPA - Wulansari, Wiwin; Nurmilawati, Mumun; Utami, Budhi; Christiono, Eko Budi (Universitas Nusantara PGRI Kediri, 2020)
In Indonesia, 21st century education has 4 skills, namely creative thinking, critical thinking, collaboration, and communication skills. 21st Century skills are applied through the K-13 curriculum which requires students to be active in learning. It is expected that students will be able to have 21st century skills including communication and argumentation skills. Communication skills are important for students to help convey, listen and understand the meaning of knowledge, values, attitudes and attention. Argumentation skills are important for students to help them argue rationally, so that other people can accept these opinions. Instruments of communication and argumentation skills of students are made as a tool to measure student skills, and instrument of validation makes it easier to collect data with the results more complete, good, systematic and easy to process. The research instrument used was an instrument of communication skills and student argumentation. This study aims to determine the validation criteria of communication skills and argumentation instruments for biology students of XI MIPA high school students. The method used is descriptive method. Based on the data obtained from the research results showed that the level of validation based on the experts of communication skills and argumentation of biology students in class XI MIPA high school including the criteria of Good (B) with a value of 25, whereas according to practitioners the communication skills and argumentation instruments of class XI MIPA high school students including the criteria of Very Good (SB) with a value of 26.